Energy Abundance or Environmental Worries? Analyzing Public Support for Fracking in the United States. Issue 1 (January 2014) - Davis, Charles; Fisk, Jonathan M.
Abstract This paper provides an analysis of public attitudes toward fracking use and policies with an eye toward factors that help us account for differing levels of support. Using data from a national survey of American adults, we found that women and people residing in urban areas are slightly more inclined to oppose fracking and to favor more regulation in terms of drilling operations and company chemical disclosure requirements than men or people living in rural areas. Our key findings, however, are that opposition to fracking and support for current or increased levels of regulation are strongly related to Democratic Party identification and to pro‐environmental policy attitudes. We conclude by suggesting that a tendency for people to view fracking as an environmental rather than an energy issue has potentially important implications for the implementation of locally based regulatory requirements.